PD.01 Stepped wedge cluster trial to evaluate training to community midwives to improve membrane sweeping to reduce induction of labour. (9th June 2014) - Kenyon, S; Dann, S; Clarke, P; Hogan, A; Jenkinson, D; Hemming, K
Abstract : Background: NICE Induction of Labour Guideline 1 recommends sweeping of the membranes is undertaken at term to reduce induction of labour. Local audit at two Maternity Units in the West Midlands suggested this was not being undertaken. Design and population Stepped wedge cluster randomised controlled trial of 10 midwifery teams, including 2, 864 low risk women over 39+4 gestation to evaluate training session. Sample size calculations suggested power 2 to detect a 10% absolute increase in proportion of women swept from baseline of 20–60%. Methods: Timing of training was randomly allocated using a stepped wedge cluster design, analysed using generalised linear mixed models. Data collected included maternal characteristics, whether membrane sweeping was offered / accepted for three months before and after training. Outcomes: Primary outcomes: numbers of women offered and accepting membrane sweeping and the average number of sweeps per woman. Secondary outcomes included membrane sweeping offered but declined no record of membrane sweeping and possible influence of selected maternal characteristics. Results: 2787 women were analysed. Baseline characteristics were similar between the two periods. No differences in the primary outcome of numbers of women being offered and accepting membrane sweeping (44.4% vs. 46.8% (Relative risk (RR) 0.90 (0.71, 1.13)), nor in the average number of membrane sweeps being undertaken (0.603 vs. 0.627, RR 0.83 (0.67, 1.01)). No difference in any secondary outcome or planned subgroup comparison. Conclusions: The trial illustrates the usefulness of this design in the robust evaluation of service delivery interventions- without which the training may have been thought to improve sweeping. References: National Institute for Health and Clinical Excellence. Induction of labour. London NICE 2008. http://guidance.nice.org.uk/CG70 Hussey MA, Hughes JP. Design and analysis of stepped wedge cluster randomized trials. Contemp Clin Trials . 2007 Feb;28(2):182–91. Epub 2006 Jul 7